Obsesi Terhadap Artis Pada Remaja Thai Enthusiast - Bayani Rahmawati, Betha; Saut H Hutahaean, Erik; Fahrudin, Adi (Jurnal Syntax Fusion, 2023)
Teenagers currently looking for their identity are fond of idol artists to be used as role models. This makes teenagers have a love or obsession with their idol artists so that they imitate their idol artists in living their daily lives. Increased focus influences adolescent behavior; this study aims to analyze the obsession with artists in Thai enthusiast youth with 133 respondents in adolescents who experience obsession with their idol artists based on availability to fill out a questionnaire. This study used the Celebrity Worship Scale (CWS) data analysis by analyzing obsession categories and correlation analysis techniques. The results show that obsession among Thai enthusiast teenagers is not low; this happens because the scope of adolescents can have a relatively high level of focus.